Validation Tool for Chemistry Teaching Innovations: Polytomous Rasch, Confirmatory Factor, and Reliability Analyses - Joje Mar Sanchez (Scientia Publica Media, 2025)
The study developed and validated the Chemistry Teaching Innovations Validation (CTIV) tool to meet the changing needs of chemistry teaching and enhance student engagement and understanding. The CTIV tool, built on the ADDIE concept, has five main components: pedagogical approach, content relevance, technology integration, assessment strategies, and teacher support and professional development. Item creation, scale formulation, and scale evaluation were all part of the validation process, including thorough testing for validity and reliability. Seven experts validated the created items, fifteen in-service teachers further improved and verified the items as included in the scale, and 264 in-service teachers participated in the pilot-testing of the revised tool. The CTIV was evaluated using various statistical analyses, including the infit and outfit values, which confirmed its reliability. The robustness of the instrument was validated by strong Cronbach’s alpha values and confirmatory factor analysis (CFA), which showed good internal consistency and precise measurement of the desired components. The CTIV tool offers teachers a systematic way to assess and use teaching innovations, guaranteeing conformity to curricular requirements and improving the quality of Chemistry education. With the help of this comprehensive validation tool, which connects theory and practice in education, Chemistry and Science classrooms can become more productive and interesting places to learn.